The Experience of Parents When they Find Out that their Child has Autism: A Phenomenological Study - Zandi, Shirdel; Jenabi, Ensiyeh; Bashirian, Saeed; Mohammadi, Reza; Karbin, Fatemeh; Khazaei, Salman (Current Psychiatry Research and Reviews, 2025)
BackgroundMothers, as vital and important individuals in their children's lives, experience various struggles, emotions, and experiences in relation to their child's autism diagnosis. This study aims to provide an in-depth understanding of mothers' experiences in dealing with the diagnosis of autism in their child using a phenomenological approach.MethodsIn this study, a qualitative phenomenological approach was used, and purposeful sampling was employed until data saturation was achieved. The participants were selected from mothers who sought their children's participation in rehabilitation classes at the Autism Spectrum Disorder Research Center in Hamedan, Iran. Unstructured interviews were conducted as the method of data collection. The descriptive method of Colaizzi was utilized for analyzing the obtained data.ResultsTwelve participants took part in this study. The average age of the participants was 35.16 years. The analysis of mothers' lived experiences in dealing with their child's autism diagnosis using a descriptive phenomenological approach revealed four main themes: fear of the child's future, worry about social harassment, emergence of emotional shock, and fear of trouble.ConclusionThe results of this study demonstrated that concern for the child's future, worry about social harm, experiencing emotional shock, and fear of being trapped were the major challenges faced by mothers upon learning about their child's positive autism diagnosis. Therefore, professionals, policymakers, and regulatory organizations should pay attention to the issues raised in parents' experiences in order to provide appropriate healthcare services for children with autism and their families.
Keywords: child' s autism diagnosis